Environmental Balance and its Impact on Sustainable Development Goals in Green Chemistry Education: A Quantitative Analysis - Jusniar Jusniar; Vika Puji Cahyani; Zuhrah Adminira Ruslan; Hastuti Agussalim; Nurul Ilmi (Universitas Syiah Kuala, in collaboration with the Perkumpulan Pendidik IPA Indonesia (PPII), (MoU), 2025)
This study explores the role of environmental balance in achieving the sustainable development goals (SDGs) in the context of advanced chemistry education. Despite the recognized importance of life harmony, diversity, and interdependence for sustainability, the specific impact of these factors in chemistry education has not been extensively studied. A quantitative pre-experimental design (one group pretest-posttest) was employed with 24 students enrolled in a sustainability-based green chemistry course. The research used a 1-5 Likert scale questionnaire to assess three variables: environmental balance (X2), harmony of life and diversity (X1), and interdependence (X3). Data were analyzed using SmartPLS 4 software. The results show that environmental balance (X2) has a positive effect on SDGs achievement (coefficient = 0.630, p = 0.053), indicating its importance in promoting sustainable behaviors. However, the variables of life harmony and diversity (X1) and interdependence (X3) did not show significant effects. These findings underscore the need to integrate environmental education into chemistry curricula, highlighting its potential to influence SDG-related outcomes. This research contributes to the understanding of how environmental awareness, especially within green chemistry education, can drive progress toward sustainability goals